2022
DOI: 10.1089/jir.2021.0222
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Matrix Metalloproteinases and TGF-β in COVID-19 Severity and Sequelae

Abstract: The costs of coronavirus disease 2019 (COVID-19) are devastating. With millions of deaths worldwide, specific serological biomarkers, antiviral agents, and novel therapies are urgently required to reduce the disease burden. For these purposes, a profound understanding of the pathobiology of COVID-19 is mandatory. Notably, the study of immunity against other respiratory infections has generated reference knowledge to comprehend the paradox of the COVID-19 pathogenesis. Past studies point to a complex interplay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 153 publications
0
18
0
Order By: Relevance
“…Under steady-state conditions, MMPs are poorly expressed in tissues. However, upon injury, inflammation, extracellular matrix turnover, and repair, their expression is enhanced ( 33 ). It has been also reported that overactivation of MMPs may contribute to the dengue pathogenesis and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under steady-state conditions, MMPs are poorly expressed in tissues. However, upon injury, inflammation, extracellular matrix turnover, and repair, their expression is enhanced ( 33 ). It has been also reported that overactivation of MMPs may contribute to the dengue pathogenesis and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that overactivation of MMPs may contribute to the dengue pathogenesis and disease severity. In addition, few other studies reported that MMPs might significantly impact the pathogenesis of respiratory viral infections including MIS-C and COVID-19 ( 33 ). In addition, studies in adult COVID-19 have reported that circulating levels of MMP-7 are potential biomarkers of disease severity in patients requiring invasive mechanical ventilation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue damage during SARS-CoV-2 lung infection is associated with activation of members of the MMPs family ( 28 , 29 ). Targeting MMPs pathway has been proposed as therapeutic strategy to counterbalance the host marked pro-inflammatory response to the SARS-CoV-2 infection ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that matrix metalloproteinase family members (MMPs), MMP8 and MMP27, were highly correlated. It has been reported that MMPs contribute to the COVID-19 severity (5153). Taken together, our findings indicate the critical roles of S100 family members and other genes (e.g., MMPs) in the progression of COVID- 19.…”
Section: Resultsmentioning
confidence: 99%